Quantifying weight loss program preferences of men working in trade and labor occupations: A discrete choice experiment - Melissa M. Crane; Surrey M. Walton; Sumihiro Suzuki; Bradley M. Appelhans (Wiley, 2023)
Abstract Objective Men who work in skilled and unskilled trades and labor occupations (i.e., blue‐collar occupations), have high rates of obesity and associated comorbidities but are underrepresented in weight loss programs. A first step in engaging this group is to better understand their preferences for weight loss programs. Methods Respondents were men working in trade and labor occupations, with overweight/obesity, and an interest in losing weight. A discrete choice experiment was developed, and the data were analyzed using mixed logit model. Respondent characteristics were tested as effect modifiers. Results Respondents (N = 221, age (M ± SD) 45.0 ± 12.6, BMI 33.3 ± 6.3, 77% non‐Hispanic white) working in a variety of occupations (construction 31%, manufacturing 30%, transportation 25%, maintenance/repair 14%) participated in this study. Results indicate preferences for programs that encourage making smaller dietary changes, are delivered online, and do not incorporate competition. Results were consistent across sensitivity analyses and most respondent groups. Conclusions The results suggest specific ways to make weight loss programs more appealing to men in trade and labor occupations. Using experimental methods to quantify preferences using larger, more representative samples would further assist in tailoring behavioral weight loss programs for under‐reached populations.